(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Plants of the genus Alchemilla are well known for their pharmacological effects. Alchemilla smirnovii Juz., also known as lady’s mantle possessed high growth-inhibiting properties against cancer cells according to earlier reports. We aimed to explore the anticancer modulatory effect of A. smirnovii extract toward 5-fluorouracil and elucidate the possible mechanism of its cytotoxic action in the HeLa cancer cell model. Synergistic interactions of plant extract with the chemotherapeutic agent were assessed by MTT assay. Based on obtained data the ethanol extract of A. smirnovii exhibits synergistic effects, enhancing the growth-inhibiting properties of 5-fluorouracil when used together. Additionally, the extract leads to a reduction in arginase activity and an elevation in the level of MDA․ This implies that A. smirnovii induces oxidative stress, and can potentially cause apoptosis in cancer cells.